2000
DOI: 10.1111/j.1600-0854.2000.11207.x
|View full text |Cite
|
Sign up to set email alerts
|

Rab3A and Rab3D Control the Total Granule Number and the Fraction of Granules Docked at the Plasma Membrane in PC12 Cells

Abstract: Rab proteins are Ras-like GTPases that regulate traffic along the secretory or endocytic pathways. Within the Rab family, Rab3 proteins are expressed at high levels in neurons and endocrine cells where they regulate release of dense core granules and synaptic vesicles. Immunoelectron microscopy shows that Rab3A and Rab3D can coexist on the same granule before and after docking. Using electron microscopy of transfected PC12 cells, we report that expression of wild-type Rab3A (or Rab3D) increases the total numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
28
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
(78 reference statements)
11
28
0
Order By: Relevance
“…In light of a recent study on PC12 cells by Martelli and colleagues our data strongly support this idea. They showed that the overexpression of a rab3a mutant protein deficient in GTP hydrolysis led to a decrease in the total number of SGs in the vicinity of the PM (Martelli et al, 2000). This is in agreement with our finding of a reduction in cortical localisation in the presence of the tail fragment of myosin Va.…”
Section: Existence and Recruitment Of Motor Protein Complexessupporting
confidence: 83%
“…In light of a recent study on PC12 cells by Martelli and colleagues our data strongly support this idea. They showed that the overexpression of a rab3a mutant protein deficient in GTP hydrolysis led to a decrease in the total number of SGs in the vicinity of the PM (Martelli et al, 2000). This is in agreement with our finding of a reduction in cortical localisation in the presence of the tail fragment of myosin Va.…”
Section: Existence and Recruitment Of Motor Protein Complexessupporting
confidence: 83%
“…The observation that Ca 2ϩ acts in the final stage of exocytosis, which was also identified in the Rab3A knock-out as the point where the function of Rab3A becomes apparent, reconciles the knock-out data and the PC12 cell transfection data. This observation also suggests the reason that a decrease in the number of total and docked vesicles was observed in transfected PC12 cells expressing Rab3A and 3D (20). Although viewed together, the results reported here and previously argue for a general role of Rab3 proteins in the final stage of exocytosis, the mechanism involved is still unclear.…”
Section: Discussionmentioning
confidence: 47%
“…In this regard, Rab3 proteins are similar to Rab11b, which we recently found to be the only Rab protein tested among multiple such proteins that inhibited exocytosis. 2 Overall, the available data reported in this and other studies (12,14,20) indicate that Rab3A, Rab3B, Rab3C, and Rab3D are functionally comparable based on similar localizations, a high degree of sequence homology, and equivalent inhibition of exocytosis in transfected PC12 cells. Clearly there are major differences in the cells and tissues that express the different Rab3 isoforms and possibly also in the functions of Rab3 proteins, because the biogenesis and fusion of secretory vesicles in exocrine glands containing Rab3D exhibit quite different properties from the biogenesis and fusion of endocrine and neuronal secretory vesicles.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Synaptic vesicles fail to cluster near release sites in C. elegans and mouse Rab3 mutants (Nonet et al, 1997;Leenders et al, 2001), and overexpression of Rab3 in PC12 cells increases the number of docked granules (Martelli et al, 2000). The yeast Rab3 homolog Ypt7p interacts with a complex containing the UNC-18 homolog Vps33p, and another yeast Rab3 homolog, Ypt1p, interacts genetically with the UNC-18 homolog Sly1p (certain Sly1 mutations bypass loss of Ypt1p) (Ossig et al, 1991).…”
Section: Dockingmentioning
confidence: 99%